iTRAQ-Based Proteomic Analysis of Sublethally Injured Escherichia coli O157:H7 Cells Induced by High Pressure Carbon Dioxide - Bi, Xiufang; Wang, Yongtao; Hu, Xiaosong; Liao, Xiaojun (Frontiers in Microbiology, 2017)
High pressure carbon dioxide (HPCD) could cause sublethally injured cells (SICs), which may cause food poisoning and spoilage during food storage and limit its application. Therefore, the formation of SICs of Escherichia coli O157:H7 was investigated by isobaric tag for relative and absolute quantification (iTRAQ) proteomic methods in this study for better controlling the SICs induced by HPCD. A total of 2446 proteins was identified by iTRAQ, of which 93 and 29 were significantly differentially expressed in the SICs compared with live control cells (CKL) and dead control cells (CKD), respectively. Among the 93 differentially expressed proteins (DEP) in the SICs compared with CKL, 65 proteins showed down-regulation and 28 showed up-regulation. According to the comprehensive proteome coverage analysis, the SICs survived under HPCD by reducing carbohydrate decomposing, lipid transport and metabolism, amino acid transport and metabolism, transcription and translation, DNA replication and repair. Besides, the SICs showed stress response, DNA damage response and an increased carbohydrate transport, peptidoglycan synthesis and disulfide bond formation to HPCD. Among the 29 DEP in the SICs compared with CKD, 12 proteins showed down-regulation and 17 showed up-regulation. According to the comprehensive proteome coverage analysis, the SICs survived under HPCD by accumulation of cell protective agents like carbohydrates and amino acids, and decreasing transcription and translation activities. Results showed that the formation of the SICs with low metabolic activity and high survival ability was a survival strategy for E. coli O157:H7 against HPCD.